Influenza and respiratory syncytial viral infections in Malaysia: Demographic and clinical perspective - Rahman M.M.; Wong K.K.; Hanafiah A.; Isahak I. (2024)
Objective: Respiratory infections represent a major public health problem worldwide. The study aimed to determine the prevalence of respiratory syncytial and influenza virus infections and analyzed in respect to demography and clinical perspective. Methods: The specimens were processed by cell culture and immunofluorescent assay (IFA) and real-time reverse transcriptase-PCR (rRT-PCR) for detection of respiratory viruses. Results: Out of 505 specimens 189 (37.8%) were positive, in which RSV was positive in 124(24.8%) cases and influenza A was positive in 65(13%) cases. Positive cases for influenza virus A and RSV were analyzed based on demography: age, gender, ethnicity and clinical symptoms. There were no significant differences among gender, ethnicity and clinical symptoms in both RSV and influenza A virus infections. It was observed that children below 3 years of ages were more prone to RSV infections. On the contrary, influenza virus A infected all age groups of humans. Conclusion: RSV infects mostly child below 3 years of age and influenza virus infects all age group. No specificity of RSV and influenza infection in relation to demography.